Performance Comparison of Infection Prediction Scores in a South African Neonatal Unit: A Retrospective Case-Control Study - Lloyd, Lizel Georgi; Dramowski, Angela; Bekker, Adrie; Malou, Nada; Ferreyra, Cecilia; Van Weissenbruch, Mirjam Maria (Frontiers in Pediatrics, 2022)
Background and objectives Infection prediction scores are useful ancillary tests in determining the likelihood of neonatal hospital-acquired infection, particularly in very low birth weight (<1500 g) infants who are most vulnerable to hospital-acquired infection and have high antibiotic utilization rates. None of the existing infection prediction scores were developed for or evaluated in South African very low birth weight neonates. Methods We identified existing infection prediction scores through literature searches and assessed each score for suitability and feasibility of use in resource-limited settings. Performance of suitable scores were compared using a retrospective dataset of very low birth weight infants (2016-2017) from a tertiary hospital neonatal unit in Cape Town, South Africa. Sensitivity, specificity, predictive values, and likelihood ratios were calculated for each score. Results Eleven infection prediction scores were identified, but only five were suitable for use in resource-limited settings (NOSEP1, Singh, Rosenberg and Bekhof scores). The five selected scores were evaluated using data from 841 episodes of hospital-acquired infection in 659 very low birth weight infants. The sensitivity for the scores ranged between 3% (NOSEP1 ≥ 14; proven and presumed infection), to a maximum of 74% (Singh score ≥1; proven infection). The specificity of these scores ranged from 31% (Singh score ≥1; proven and presumed infection),) to 100% (NOSEP1 ≥11 and ≥14, NOSEP-NEW ≥11; proven and presumed infection) Conclusions Existing infection prediction scores did not achieve comparable predictive performance in South African very low birth weight infants and should therefore only be used as an adjunct to clinical judgement in antimicrobial decision making. Future studies should develop infection prediction scores that have high diagnostic accuracy and are feasible to implement in resource-limited neonatal units.